Influence of prebiotic biopolymers on physicochemical and sensory characteristics of yoghurt. (April 2021) - Yu, Daeung; Kwon, Gicheol; An, Jihye; Lim, Young-Soon; Jhoo, Jin-Woo; Chung, Donghwa
Abstract: Yoghurts were prepared by fermentation in the absence (control) or presence of different concentrations of inulin, tragacanth gum, or gellan gum, and effects of the biopolymers on physicochemical and sensory characteristics of yoghurts during cold storage were examined. No significant difference in pH, colour, total solid, and bacterial viability was observed among all the yoghurts prepared. Rheological analysis revealed that yoghurts prepared with biopolymers were pseudoplastic, and firmness and apparent viscosity were greater in yoghurts with added biopolymer than in control. Syneresis was weaker in yoghurts with added biopolymer, and showed a decreasing trend with biopolymer concentration but an increasing pattern with storage time due to gel shrinkage. Yoghurts with added biopolymer showed homogeneous and more compact microstructures than control. Yoghurt prepared with 0.01% tragacanth gum exhibited the best sensory scores. Results demonstrated that small amounts of tragacanth gum could effectively replace gellan gum as a thickener of synbiotic yoghurt.